DEVELOPMENT OF HYPEBID MARKETPLACE INFORMATION SYSTEM WITH REAL-TIME ONLINE AUCTION FEATURE - Jovan Avriananta; Arief Hermawan (Jurnal Riset Informatika, 2025)
Conventional auctions still face a number of challenges, such as limited access, unclear processes, and low time efficiency. Auction participants are generally required to be physically present, which limits the number of participants and reduces transparency and transaction speed. Based on this background, this study aims to develop HypeBid, a web- and mobile-based marketplace information system that supports online and real-time auction processes. This system is built using a client-server architecture with React Native, Express.js, PostgreSQL, and Supabase technologies. Development was carried out through stages of needs analysis, system design, and implementation of key features such as user registration, product verification, live bidding, integrated payment systems, and transaction reports. System testing was conducted using the black box testing method involving two groups of users, namely buyers and auction officers. The test results showed that all features functioned as expected, without any functional errors. Thus, HypeBid is considered to be a clearer, more flexible, and efficient alternative solution compared to conventional auction methods.